How Multicultural School Counselors Prepare Social–Emotional Development Program in Junior High School? - Astuti, Budi; Purwanta, Edi; Bhakti, Caraka Putra; Sunarti; Kurniasih, Cucu; Lestari, Rizqi; Putra, Bela Janare (Department of Guidance and Counseling, FIP, Undiksha, 2024)
This study is driven by the urgent need to develop social-emotional development programs in Indonesian junior high schools, considering the significant changes that occur during adolescence and the challenges faced in multicultural contexts. Effective social-emotional development programs can help students manage emotions, strengthen social relationships, and enhance their mental well-being in the school environment. The primary objective of this research is to explore how multicultural school counselors prepare social-emotional development programs that meet the needs of junior high school students. This study employs a survey method with a quantitative approach, involving 126 school counselors from various provinces in Indonesia as research subjects. Data were collected through an online questionnaire distributed via Google Forms, utilizing instruments covering needs assessment, reference material development, and system support. Data analysis was conducted using descriptive statistics to identify patterns and trends in social-emotional program development in schools. The results indicate that most counselors use needs assessments as a basis for developing their programs and leverage various resources, including peer documents, digital media, and collaboration with the school community. The study concludes that a needs-based approach is crucial in developing social-emotional programs.